2017
DOI: 10.21873/anticanres.11304
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of CD163+ Macrophages in Tumor Stroma and CD8+ T-Cells in Cancer Cell Nests in Invasive Extrahepatic Bile Duct Cancer

Abstract: Abstract. Aim: The aim of this study was to examine the clinicopathological influence of tumor-infiltrating cluster of differentiation (CD) 163 + macrophages and CD8 + T-cells, and to clarify the prognostic effects of these cells in patients with invasive extrahepatic bile duct cancer (EHBC). Materials and Methods: The numbers of CD8 + T-cells in cancer cell nests and CD163 + macrophages in tumor stroma (hazard ratio=0.127, p<0.001) and in patients treated with adjuvant chemotherapy (hazard ratio=0.139, p=0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 27 publications
2
33
0
Order By: Relevance
“…It possesses potent antitumor immune function that could inhibit progression of several tumors [ 14 ], and elevated level of lymphocyte was reported to be associated with favorable prognosis of a variety of tumors [ 15 ]. It was also reported that several subtypes of tumor infiltrating lymphocyte were associated with better outcomes of a variety of tumors [ 16 18 ], including CD8+ T cells [ 19 ] and memory T cells [ 20 ]. However, some subsets of T cells were associated with progression and unfavorable prognosis of tumors, such as regulatory T cells [ 21 ] and Th17 cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…It possesses potent antitumor immune function that could inhibit progression of several tumors [ 14 ], and elevated level of lymphocyte was reported to be associated with favorable prognosis of a variety of tumors [ 15 ]. It was also reported that several subtypes of tumor infiltrating lymphocyte were associated with better outcomes of a variety of tumors [ 16 18 ], including CD8+ T cells [ 19 ] and memory T cells [ 20 ]. However, some subsets of T cells were associated with progression and unfavorable prognosis of tumors, such as regulatory T cells [ 21 ] and Th17 cells [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…TAMs at different locations within the tumor may have different impacts on GC progression [ 14 ]. TAMs infiltration into tumor stroma has significant clinical relevance in GC, indicating the importance of not only studying the number but also studying the locations [ 15 ]. TAMs infiltration at invasive front could influence cancer metastasis through epithelial-mesenchymal transition (EMT) mechanism [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, TAMs facilitate tumor regrowth, revascularization, spread after the treatment 30,31 . Their tumor-promoting functions are supported by clinical association of TAM infiltration with poor prognosis in most human cancer types, including ovarian cancer [32][33][34] . Therefore, various strategies have been developed to exploit TAMs for anti-cancer therapies 25,35 .…”
mentioning
confidence: 99%